Energy governance in Portugal - Guerreiro, L. (2022)
Portugal is in the middle of a major transformation of its energy supply, which has been shaped by internal resource constraints, growing environmental concerns, and the dynamics of European integration. Portugal’s past choices – the investment in hydropower and the refusal of nuclear energy – and the lack of an endowment of resources have constrained the Portuguese energy policy. With the accession to the European Union in 1986, environmental concerns moved up the Portuguese policy agenda. The EU’s push for a common electricity market influenced a set of policies oriented toward the liberalization of the energy market, which was centralized, monopolistic, and public owned. The investment in renewable energy gained momentum in the 2000s, led by the Portuguese government and EDP, the (then) publicly owned energy company, supported by a public discourse on climate change and energy policy imbued with economic rationality. The financial crisis that hit Portugal in 2010 led to a temporary stall in the promotion of the use of energy from renewable energy sources (RES), but new market-based support schemes, such as photovoltaic solar auctions, have fostered the recent new investment in renewables.